2018
DOI: 10.3390/molecules23030605
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of 8-Nitroguanine in DNA by Chemical Derivatization Coupled with Online Solid-Phase Extraction LC-MS/MS

Abstract: 8-Nitroguanine (8-nitroG) is a major mutagenic nucleobase lesion generated by peroxynitrite during inflammation and has been used as a potential biomarker to evaluate inflammation-related carcinogenesis. Here, we present an online solid-phase extraction (SPE) LC-MS/MS method with 6-methoxy-2-naphthyl glyoxal hydrate (MTNG) derivatization for a sensitive and precise measurement of 8-nitroG in DNA. Derivatization optimization revealed that an excess of MTNG is required to achieve complete derivatization in DNA h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…24 Nevertheless, RNS are mostly produced under inflammatory conditions in inflammatory and epithelial cells; activation of iNOS leads to an abundant formation of NO which in turn is converted into various RNS, including ONOO À . 25,13,14 However, inflammation and the concomitant immune response, impelled by ionizing irradiation, depend on several factors including the radiation type, dose, intensity/fractionation and total cumulative dose. 26 Recent studies have demonstrated an association between NO pathway and immune response induced by irradiation while both of them are regulated in a radiation-dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…24 Nevertheless, RNS are mostly produced under inflammatory conditions in inflammatory and epithelial cells; activation of iNOS leads to an abundant formation of NO which in turn is converted into various RNS, including ONOO À . 25,13,14 However, inflammation and the concomitant immune response, impelled by ionizing irradiation, depend on several factors including the radiation type, dose, intensity/fractionation and total cumulative dose. 26 Recent studies have demonstrated an association between NO pathway and immune response induced by irradiation while both of them are regulated in a radiation-dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…由此可见, 氧化衍生化主要用于对不饱和脂质 C=C 异构体的分析研究, 该技术的不断拓展与应用极 大地促进了脂质组学的发展, 对脂质异构体研究、疾 病机理的研究具有重要意义. (8-(diazomethyl) quinoline, 8-DMQ) [156] 、 2-溴-1-(4-二甲 氨基苯基)乙酮(2-bromo-1-(4-dimethylamino-phenyl)ethanone, BDAPE) [150] 、丙酮 [148] 、2-溴-1-(4-二乙基氨 基 苯 基 )-乙 酮 (2-bromo-1-(4-dimethylamino-phenyl)ethanone, BDEPE) [152] 、 6-甲 氧 基 -2-萘 乙 二 醛 (6-methoxy-2-naphthyl glyoxal hydrate, MTNG) [188] 、 三 ( 三 苯 基 膦 金 ) 氧 鎓 四 氟 硼 酸 (tris(triphenylphosphinegold)oxonium tetrafluoroborate, [Ph3PAu]3O + BF4 -) [162] 、 三 菲 咯 啉 镁 络 合 物 (trisphenanthroline magnesium complex dications, PMCD) [163] 、异丁酸 [189] 等, 它们在 MS 检测分析中发挥重要作用. 应用于 MS…”
Section: F O R R E V I E W O N L Yunclassified
“…[19][20][21] The major lesion 8-NO2-G is labile (half-life ∼1.6 and 2.4 h for single-and double-stranded DNA, respectively) and undergoes spontaneous depurination to form abasic sites which ultimately lead to DNA strand breaks. [22] 8-NO2-G is also known to be mutagenic. [23] O 6 -alkylguanine-DNA alkyltransferase (AGT, MGMT) is a ubiquitous repair protein involved in the direct reversal of mutagenic DNA lesion O 6 -methylguanine and to a lesser extent O 4methylthymine to the natural base guanine and thymine, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The major lesion 8-NO2-G is labile (half-life ∼1.6 and 2.4 h for single-and double-stranded DNA, respectively) and undergoes spontaneous depurination to form abasic sites which ultimately lead to DNA strand breaks. [22] 8-NO2-G is also known to be mutagenic. […”
Section: Introductionmentioning
confidence: 99%